Minimum wage channels of adjustment - Barry T. Hirsch; Bruce E. Kaufman; Tetyana Zelenska (Institute for the Study of Labor (IZA), 2011)
The economic impact of the 2007-2009 increases in the federal minimum wage (MW) is analyzed using a sample of quick-service restaurants in Georgia and Alabama. Store-level biweekly payroll records for individual employees are used, allowing us to precisely measure the MW compliance cost for each restaurant. We examine a broad range of adjustment channels in addition to employment, including hours, prices, turnover, training, performance standards, and non-labor costs. Exploiting variation in the cost impact of the MW across restaurants, we find no significant effect of the MW increases on employment or hours over the three years. Cost increases were instead absorbed through other channels of adjustment, including higher prices, lower profit margins, wage compression, reduced turnover, and higher performance standards. These findings are compared with MW predictions from competitive, monopsony, and institutional/behavioral models; the latter appears to fit best in the short run.
urn:nbn:de:101:1-201112136806
Keywords: J20; J30; 330; minimum wages; employment; labor market adjustments; labor market theories; Mindestlohn; Wirkungsanalyse; Schnellgastronomie; Anpassung; Beschäftigungseffekt; USA